A Comparative Analysis of Indonesia's Tobacco Competitiveness in the International Market Based on HS Codes 2401.10, 2401.20, and 2401.30 - Bayu Eka Wicaksana; Ludivica Endang Setijorini; Albert Gamot Malau; Chikita Lestari Saputriningsih (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Indonesia's strategic geographical position and tropical climate provide optimal conditions for various plantation commodities, tobacco being a key contributor to the national economy. Despite its significant role in exports and state revenue through excise taxes, fluctuations in Tobacco Excise Duty (CHT) rates have raised concerns about their impact on farmers' income and global competitiveness. This study aims to analyze the comparative competitiveness of tobacco commodities under HS codes 2401.10 (manufactured tobacco or tobacco remnants from primary tobacco that are not stemmed/stripped), 2401.20 (tobacco that is partly or wholly stemmed/stripped), and 2401.30 (tobacco refuse). The method used to measure the comparative competitiveness of each tobacco HS category is by calculating the Revealed Comparative Advantage (RCA) value. The observation period and central destination countries were determined purposefully, considering 2014 was when the trial increase in national cigarette excise was implemented. The data range in this study spans from 2014 to 2022 (time series), and the central destination countries were determined based on the ranking of countries with the highest tobacco export value from Indonesia each year. Indonesia's tobacco exports showed dynamic trends between 2014 and 2022, with Sri Lanka, Belgium, and the Dominican Republic emerging as the leading destinations for HS codes 2401.10 and 2401.20, while the United States, Vietnam, and Malaysia dominated under HS code 2401.30. Despite its strong competitiveness, fluctuations in export volumes and declining selling prices, especially in the Dominican Republic, indicate the influence of global market conditions, regulatory frameworks, and changing demand patterns. These findings underscore the importance of adaptive trade strategies to strengthen Indonesia's position in the global tobacco market.